GAMBARAN DUKUNGAN KELUARGA PADA PASIEN ULKUS DIABETIKUM DI RUMAT UNIT KENDAL - Hayyuni Rozyana Monika Sari; Eko Suprapto; Elis Hartati (LPPM Universitas BSI, 2023)
Diabetes Mellitus (DM) is a chronic disease characterized by increased blood glucose levels in the body which occurs as a result of the pancreas being unable to produce insulin effectively. Diabetic Foot Ulcers (DFU) is a dangerous complication of diabetes mellitus and requires special wound care. Family involvement during the treatment of DFU is needed to help control various risk factors for complications and good management of diabetes mellitus. Family support for DFU patients can increase motivation, self-confidence, quality of life and health status. The purpose of this study was to determine the description of family support in patients with diabetes mellitus with diabetic foot ulcers in the Rumat Kendal. This research uses descriptive quantitative observational research with survey methods. The research sample consisted of 10 diabetes mellitus patients with DFU who performed wound care at the Rumat Kendal. Data were collected using the Hensarling's Diabetes Family Support Scale (HDFSS) questionnaire. The method of analysis uses descriptive statistics. The results of the study found that most of the patients received good family support. The highest dimension of family support is emotional support and the lowest is appreciation support and information support. The conclusion in this study is that good family support is considered capable of increasing one's confidence in one's ability to perform self-care, increase self-confidence, increase motivation, and improve one's health status.